Exploring Specialist Palliative Care Practitioner Perspectives on the Face Validity of the Attitude to Health Change Scales in Assessing the Impact of Life-limiting Illness on Patients and Carers - Machin, Linda; Walshe, Catherine; Dunleavy, Lesley (Journal of palliative care, 2024)
Background: Identifying and assessing vulnerability and resilience through reflexive reactions and conscious coping responses to life-limiting illness is an important, but rarely assessed, component of care. The novel Attitude to Health Change scales can contribute to this, but require fuller development and testing. Objectives: Exploring face validity of the Attitude to Health Change Scales (patient and carer versions) from the perspective of specialist palliative care professionals. Design: A two-stage study: (i) focus groups to explore experiences of scale use and wording, (ii) online survey to gather preferences on possible scale modifications. Focus group data were analysed using framework analysis. A hermeneutic approach was used to modify the wording of the scales, ensuring adherence to the underpinning concepts used in the design of the scale, congruence with the palliative care context, and simplicity of language. Setting/Subjects: Specialist palliative care practitioners in UK hospice settings who had been involved in pilot use of the scales in clinical practice. Results: 21 practitioners participated in 3 focus groups across 3 UK hospice sites, 9 of those participants responded to the survey. Four themes are presented: the importance and distinctiveness of the scales; maintaining conceptual integrity; ensuring a palliative care focus; and ensuring linguistic clarity. New iterations of the patient and carer versions of the Attitude to Health Change scales were developed. Conclusion: The scales appear to reflect the intended theoretical constructs, and are worded in a way which is congruent with the experience of specialist palliative care practitioners.